Exceptional Complex Chromosomal Rearrangements in Three Generations. (3rd February 2015) - Kartapradja, Hannie; Marzuki, Nanis Sacharina; Pertile, Mark D.; Francis, David; Suciati, Lita Putri; Anggaratri, Helena Woro; Ambarwati, Debby Dwi; Idris, Firman Prathama; Lesmana, Harry; Trimarsanto, Hidayat; Paramayuda, Chrysantine; Harahap, Alida Roswita
Abstract : We report an exceptional complex chromosomal rearrangement (CCR) found in three individuals in a family that involves 4 chromosomes with 5 breakpoints. The CCR was ascertained in a phenotypically abnormal newborn with additional chromosomal material on the short arm of chromosome 4. Maternal karyotyping indicated that the mother carried an apparently balanced CCR involving chromosomes 4, 6, 11, and 18. Maternal transmission of the derivative chromosome 4 resulted in partial trisomy for chromosomes 6q and 18q and a partial monosomy of chromosome 4p in the proband. Further family studies found that the maternal grandmother carried the same apparently balanced CCR as the proband's mother, which was confirmed using the whole chromosome painting (WCP) FISH. High resolution whole genome microarray analysis of DNA from the proband's mother found no evidence for copy number imbalance in the vicinity of the CCR translocation breakpoints, or elsewhere in the genome, providing evidence that the mother's and grandmother's CCRs were balanced at a molecular level. This structural rearrangement can be categorized as an exceptional CCR due to its complexity and is a rare example of an exceptional CCR being transmitted in balanced and/or unbalanced form across three generations.